APPONTO-PRO: um processo incremental para o aprendizado e povoamento de ontologias de aplicação - Santos, Suzane Carvalho dos (2014)
Ontologies are knowledge representation structures capable of expressing a set of entities of a domain, their relationships and axioms that are being used by modern knowledge based systems (KBS) in the decision making process. However, manual construction of ontology is expensive and subject to errors, thus a viable alternative is the automation of this process. Several techniques and tools have been developed to learn the different components of an ontology from textual sources, named concepts, hierarchies, instances, relationships, properties and axioms. However, these elements are generally acquired in a isolated manner. Due to the lack of approaches to acquire all the elements of an ontology jointly, there is a need to develop a process to make the reuse and the learning of each of the elements of an ontology in a synergistic manner. To attend this need, this work presents Apponto-Pro, an incremental learning process for populating application ontologies from textual information sources that is capable of generating a complete ontology through the integration of different techniques to generate isolated elements of an ontology. The process was evaluated through a case study that consisted in the automatic construction of Family_Law, an application ontology in the field of family law developed with Apponto-ProTool, a software tool to support Apponto-Pro that integrates the approaches that compound the whole process. This evaluation aimed to determine the effectiveness of the ontology constructed with Apponto-ProTool against an ontology manually built by a domain specialist and used as reference ontology. For this reason, the "precision"was calculated for the elements of the ontology automatically generated using the reference ontology. As a result it was found that in some cases the ontology developed with Apponto-ProTool tends to present more suitable results.